Is It Harassment? Perceptions of Sexual Harassment Among Lawyers and Undergraduate Students - Shechory-Bitton, Mally; Zvi, Liza (Frontiers in Psychology, 2020)
This study examined differences between lawyers (n = 91) and undergraduate students (n = 120) regarding their evaluation of behavior as sexual harassment (SH) and blame attributions toward offender and victim. The current study used a cross-sectional, comparative, independent measures design. Also examined was the correlation between these perceptions and belief in a just world (BJW) hypothesis. The respondents were presented with case descriptions of SH that were identical in all aspects but the perpetrator and victim’s gender (alternately depicted as male/female and female/male). Results showed that both lawyers and students agreed that the described event comprised SH, yet gender bias was evident. Both lawyers and students were more inclined to regard the behavior as SH when the vignette description depicted the perpetrator as a man (i.e., female victim) than as a woman (male victim). Gender bias was also evident in the examination of blame attributions, which were higher toward a male (vs. female) harasser. Nonetheless, the findings indicate that lawyers were less biased than students, manifested in less victim-blame and higher perpetrator blame attributions. No correlation between BJW and perceiving the vignette as SH and blame attribution was found. The findings indicate discriminatory judgments of SH based on gender. Gender-related stereotypes and sociocultural explanations are discussed.